Thoracic Responses and Injuries of Male Post-Mortem Human Subjects in a Homogeneous Rear-Facing Seat During High-Speed Frontal Impact - Kang, Yun-Seok; Baker, Gretchen H.; DeWitt, Timothy; Marcallini, Angelo; Pradhan, Vikram; Tesny, Angela; Bendig, Alex; Haverfield, Zachary; Agnew, Amanda M.; Bolte, John H. (Annals of biomedical engineering, 2025)
In recent post-mortem human subjects (PMHS) studies in a high-speed rear-facing frontal impact (HSRFFI), the PMHS sustained multiple rib fractures. The seatback structure and properties of the seats might contribute to these fractures. This study aimed to determine if a homogeneous rear-facing seat with foam-covered seatback would mitigate the risk of thoracic injury during an HSRFFI. Three male PMHS were subjected to the same previous HSRFFI pulse. The seating structure consisted of a homogeneous seatback composed of rigid plates with load cells and covered with both comfort and safety foam. The PMHS spine was instrumented with accelerometers and angular rate sensors. Two chestbands were attached at the level of the axilla and xiphoid, and strain gages and strain rosettes were attached to ribs. Whole-body kinematics were quantified using a motion capture system. PMHS1 and PMHS3 sustained 30 and 13 rib fractures, respectively, while PMHS2 did not sustain any fractures. Average maximum anterior-posterior (A-P) chest compressions ranged from 15.9 to 22.6%. Rib fractures occurred before and after the maximum A-P compression, so A-P chest compression alone did not correlate well with rib fracture outcomes. Thoracic inferior-superior (I-S) deformation relative to the T12 was 107.4 mm for PMHS1, 27.6 mm for PMHS2, and 85.1 mm for PMHS3. The direction of the maximum principal strain indicated that ribs experienced shear caused by I-S chest deformation. These results will assist with the development of countermeasures to protect occupants in a rear-facing seating configuration, along with validation of human body models.